1998
DOI: 10.1161/01.str.29.12.2549
|View full text |Cite
|
Sign up to set email alerts
|

Ataxic Hemiparesis

Abstract: Background and Purpose-Ataxic hemiparesis is a well-recognized lacunar syndrome involving homolateral ataxia with accompanying corticospinal tract impairment. Despite 30 years of clinical experience there continues to be some doubt as to the defining clinical characteristics, precise neuroanatomic localization of the syndrome, and etiologic mechanisms. Methods-We now present 45 new cases that have been analyzed for clinico-radiologic correlation and etiology. Also, all published cases from the English literatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(5 citation statements)
references
References 86 publications
0
5
0
Order By: Relevance
“…1 In another large series of AH, the infarct localizations were similar (43% pons, 13% internal capsule only, 33% thalamocapsular, and 10% striatocapsular). 2 In another series, the most common infarct locations were internal capsule, pons, and corona radiata. 3 The corona radiata localization of the lacunar infarcts seen in our 3 cases is thus not an uncommon cause of AH.…”
Section: Discussionmentioning
confidence: 93%
“…1 In another large series of AH, the infarct localizations were similar (43% pons, 13% internal capsule only, 33% thalamocapsular, and 10% striatocapsular). 2 In another series, the most common infarct locations were internal capsule, pons, and corona radiata. 3 The corona radiata localization of the lacunar infarcts seen in our 3 cases is thus not an uncommon cause of AH.…”
Section: Discussionmentioning
confidence: 93%
“…In several subsequent studies [ 4 ], AH was commonly defined as ipsilateral ataxia and hemiparesis without a sensory disturbance. Gorman et al [ 9 ] reported that 45 of 1,468 lacunar infarctions (3%) corresponded to AH, and 10 of those cases (0.7%) were due to a thalamic lesion. However, some patients with a sensory disturbance were also included.…”
Section: Discussionmentioning
confidence: 99%
“…These reorganized neurons were impaired in his recent stroke, with the subsequent infarct expansion damaging the original, non-reorganized neurons, that controlled right-sided motor function. These original neurons likely belonged to the CST and intermingled corticocerebellar fibers, leading to his ataxic hemiparesis [10]. Ideally, PET or fMRI could have delineated the exact recovery and pathophysiology of our patient's clinical course [11][12][13]; however, due to resource limitations, this was not feasible.…”
Section: Discussionmentioning
confidence: 99%